2004
DOI: 10.1081/ncn-200026036
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease Activity of the Peptides with Alternating Arginine and Leucine Residues Conjugated to Tetrathymidilate

Abstract: RNA cleaving conjugates have been prepared by attachment of oligodeoxyribonucleotide TTTT to peptides containing arginine, leucine, proline and serine residues. The highest activity was displayed by the conjugates containing peptides with alternating arginine and leucine residues (LR)4G-amide. Ribonuclease activity of the conjugates pep-T4 decreases in the order T4-(LR)4G > T4-(LR)2G > T4-(LLRR)2G > T4-(LR)2PRLRG > S2R3-Hmda-T4 > or = R5 double dagger (LR)3. According to CD spectra, the free peptide (LR)4G-ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Our recent work (Patutina et al, 2017(Patutina et al, , 2019Staroseletz, Williams et al, 2017;Williams et al, 2015) and earlier studies from other groups (Mironova et al, 2002;Mironova, Boutorine et al 2004;Mironova et al, 2006Mironova et al, , 2007Pyshnyi et al, 1997) demonstrated that the biological activity of this class of bioconjugates can only be achieved through chemical conjugation of the catalytic peptide with the oligonucleotide component. This suggested that the oligonucleotide component may induce an 'active' conformation of the peptide to make it catalytically active by some unclear molecular interactions between the oligonucleotide and peptide components.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Our recent work (Patutina et al, 2017(Patutina et al, , 2019Staroseletz, Williams et al, 2017;Williams et al, 2015) and earlier studies from other groups (Mironova et al, 2002;Mironova, Boutorine et al 2004;Mironova et al, 2006Mironova et al, , 2007Pyshnyi et al, 1997) demonstrated that the biological activity of this class of bioconjugates can only be achieved through chemical conjugation of the catalytic peptide with the oligonucleotide component. This suggested that the oligonucleotide component may induce an 'active' conformation of the peptide to make it catalytically active by some unclear molecular interactions between the oligonucleotide and peptide components.…”
Section: Resultsmentioning
confidence: 98%
“…We have recently developed a new class of catalytic bioconjugates, as synthetic ribonucleases using amphipathic peptides, which only cleave RNA when conjugated to oligonucleotide recognition motifs (Mironova et al, 2002;Mironova, Boutorine et al, 2004;Mironova et al, 2006Mironova et al, , 2007Patutina et al, 2017Patutina et al, , 2019Pyshnyi et al, 1997;Staroseletz, Williams et al, 2017;Williams et al, 2015). These RNA-targeting synthetic nucleases are chemically-engineered by conjugation of short, catalytically-inactive peptides with oligonucleotide recognition motif components, which range from fully-through poorlyto non-complementary to the target RNA, in order to produce novel biologically-active molecules capable of recognizing and cleaving RNA sequences quantitatively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mironova and co-workers have synthesized a series of POCs capable of cleaving RNAs in a sequence specific manner. The oligonucleotides 171 , 172 , and 173 with different specificities were linked to the core (catalytic) peptide sequence, [Arg-Leu] 4 -Gly, using the SPFC method to obtain the conjugate shown in Figure . The oligonucleotide and peptide fragments of these conjugates (pep− 171 , pep− 172 , and pep− 173 in Figure ) were connected by N -alkylphosphoramidate linkages between the 5‘-terminal phosphate of the oligonucleotide and the N-terminal-α-amino group of the corresponding oligopeptide.…”
Section: 3 Artificial Enzymesmentioning
confidence: 99%